Investigating the crosstalk between chronic stress and immune cells: implications for enhanced cancer therapy - Lei, YongRong; Liao, Fenghui; Tian, YiChen; Wang, YaNi; Xia, Feng; Wang, JianHua (Frontiers in Neuroscience, 2023)
Chronic stress has a substantial influence on the tumor microenvironment (TME), leading to compromised effectiveness of anti-cancer therapies through diverse mechanisms. It disrupts vital functions of immune cells that play a critical role in anti-tumor immunity, such as the inhibition of dendritic cells (DCs) and lymphocytes, while simultaneously enhancing the activity of immune cells that support tumor growth, such as myeloid-derived suppressor cells and tumor-associated macrophages. Furthermore, chronic stress exerts a significant impact on crucial mechanisms within the TME, including angiogenesis, DNA repair, hypoxia, extracellular matrix deposition, and tumor metabolism. These alterations in the TME, induced by stress, result from the activation of the hypothalamic-pituitary-adrenal axis and sympathetic nervous system, in conjunction with epigenetic modifications. In conclusion, chronic stress significantly influences the TME and impedes the efficacy of anti-cancer treatments, underscoring the importance of targeting stress pathways to improve therapeutic results.